(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The study aims to identify the factors persuading bank employees’ perception towards technology allowed banking and examining the association between the factors and demographic profile of the bankers. A measurable and qualitative approach is used in the study and data is collected from respondents who are part of the banking system across various banks through a well-structured questionnaire and interviews. The pragmatic results show that employee convenience is attained through improving operational efficiency, making decision based on cost effectiveness, better customer service and thereby higher employee morale, performance linked incentives and other perks and benefits and technical support are the main factors influencing the perception of bankers towards technology adoption in India. There are certain fundamental factors like hoax, spam, hacking, and fraud etc. affecting users and thereby the implementation of digitalization in banking is imperative. Also, the perception of bankers differs significantly in terms of the availability of technical support by type of bank. The novelty of the study completely depends upon the perception about the implication of technology enabled banking services and the influence of demographic variables on technology adoption in context to Indian bank employees has been analysed. The results will help the banks from India as well as other developing countries in creating substantial change in strategic planning to increase the adoption of technology that can empower the employees and customers indirectly. Banks can use the findings to encourage their employees to promote the use and adoption of digital banking in India.